Application of Rho Kinase Inhibitors for the Treatment of Corneal Endothelial Diseases. (2nd July 2017) - Okumura, Naoki; Kinoshita, Shigeru; Koizumi, Noriko
Abstract : ROCK (Rho kinase) signaling regulates a wide spectrum of fundamental cellular events and is involved in a variety of pathological conditions. It has therefore attracted research interest as a potential therapeutic target for combating various diseases. We showed that inhibition of ROCK enhances cell proliferation, promotes cell adhesion onto a substrate, and suppresses apoptosis of corneal endothelial cells (CECs). In addition, we reported that a ROCK inhibitor enhances wound healing in the corneal endothelium in animal models and in pilot clinical research. We also demonstrated the usefulness of a ROCK inhibitor as an adjunct drug in tissue engineering therapy as it enhances the engraftment of CECs onto recipient corneas. In 2013, we initiated a clinical trial to test the effectiveness of injection of cultured human CECs into the anterior chamber of patients with corneal endothelial decompensation. This paper reviews the accumulating evidence supporting the potency of ROCK inhibitors in clinical use, both as eye drops and as adjunct drugs in cell-based therapies, for the treatment of corneal endothelial decompensation.